A RARE CASE : HOMONYMOUS HEMIANOPIA IN CHILDREN: Poster Presentation - Case Report - Resident - RAHAYU WIDHYASTI1; Antonia Kartika Indriati; Rusti Hanindya Sari; Dianita Veulina Ginting; Prettyla Yollamanda (Majalah Oftalmologi Indonesia, 2023)
Abstract Introduction : Homonymous hemianopia (HH) is a visual field loss in the same halves of the visual field of each eye that is caused by numerous lesion affecting the retrochiasmal visual pathway. Homonymous hemianopia in children is a rare disabling condition and might be found as an initial presentation of brain tumors. Case Illustration : A 12 years old boy came with chief complaint of partially vision loss on the left side of vision accompanied by intermittent headache. Ophthalmological examination showed visual acuity of 1.0 on both eyes. Visual field examination revealed left homonymous hemianopia (figure 1). These findings were relevant to the result of his brain Computed Tomography (CT) scan, which showed vascular mass in the right occipital lobe caused by suspected arteriovenous malformation mixed diffuse type (figure 2). The patient was referred to neurosurgeon for further management. Discussion : Visual field defect depends on location of the lesion and can be used to recognize optic pathway diseases. Homonymous hemianopia occurs in retrochiasmal lesions that could happened either in adult or children. Unusual presentation of HH in children caused by brain tumor such as arteriovenous malformation. It might occur in up to 27% and can be detected radiologically with either brain CT scan or Magnetic Resonance Imaging (MRI). Conclusion : Visual field loss in pediatric patient might be challenging. Proper and prompt diagnosis is important to detect underlying condition and determine further management of the patient.